THE DEVELOPMENT OF STUDENTS’ ACTIVITY SHEET WITH GUIDED INQUIRY ORIENTATION TO TRAIN CRITICAL THINKING SKILL OF INCLUSIVE STUDENTS IN SUB MATERIALS FACTORS THAT AFFECTING REACTION RATE (UNESA Journal of Chemical Education, 2017)
This study aims to determine the validity of The Development of Students’ Activity Sheet with Guided Inquiry Orientation to Train Critical Thinking Skill of Inclusive Students in Sub Materials Factors That Affecting the Reaction Rate. The validity of the developed Students’ Activity Sheet is based on internal validity and external validity. Internal validity is reviewed from the validation result. External validity is reviewed from student responses after using Guided Inquiry-based Activity sheet to Train the Critical Thinking Skills of Inclusive Students on Sub Material Factors that Affecting Reaction Rate that developed. This research uses R & D method, but only applied until development stage. Judging from the validation result, student workesheet based on content criteria of 85.07%, 80.83% on presentation content and 83.33% on the language content. Judging from the results of student responses, the feasibility of Students’ Activity Sheet based on content criteria is 100%, 100% of presentation and language of 97.21%. Judging from the pretest and posttest results obtained classical completeness of 87.5% calculated from completeness of classical pretest of 12.5% ​​ and classical posttest of 100%. Keywords: Students’ Activity Sheet, guided inquiry, critical thinking skill, inclusive.